D. H. Lawrence's creative responses to censorship, 1915-1930 - Walker, Gregory (2025)
This thesis examines D. H. Lawrence’s creative responses to the censorship of his work over the fifteen-year period from 1915 (the year in which he had his first encounter with legal censorship) to his death in 1930. It uses the critical term ‘climate of censorship’ to conceptualise and describe how censorship functioned in the modernist period, providing a detailed analysis of censorious agents, institutions and laws, and an account of the ways in which they brought pressure to bear on Lawrence throughout his career. The thesis offers the first monograph-length analysis of Lawrence’s engagement with censorship, drawing together numerous case studies into a cohesive narrative, tracing the evolution of Lawrence’s attitudes towards, and responses to, the censorship of his work. It considers a number of under-researched aspects of the subject, including the American prosecution of Women in Love and Lawrence’s self-censorship of Lady Chatterley’s Lover as part of his abortive effort to produce a trade edition of the novel. It explains how threats of prosecution for libel limited Lawrence’s aesthetic autonomy in a manner comparable to the threat of an obscenity prosecution; it argues that the issue of libel can be considered as a part of the climate of censorship. In its analysis of Lawrence’s resistance to censorship, the thesis considers private publication as an aspect of a cultural infrastructure which arose in response to the climate of censorship. The thesis explores how Lawrence used different means of engaging with the literary marketplace to minimise the impact of censorship and access a receptive readership for his work.